ADVATE prophylaxis: post hoc analysis of joint bleeding episodes. (21st February 2014) - Valentino, L. A.; Reyes, C. M.; Ewenstein, B.; Guzmán‐Becerra, N.; Wong, W. Y.; Schoenig‐Diesing, C.; Romanov, V.
Summary Introduction The ADVATE (rAHF‐PFM) Prophylaxis Study compared the efficacy of (i) standard factor (F) VIIII prophylaxis (SP) (20–40 IU kg−1 every other day) vs. pharmacokinetic‐tailored prophylaxis (PKP) (20–80 IU kg−1 every third day) and (ii) both prophylactic regimens with on‐demand therapy (OD) in 66 previously on‐demand‐treated patients (median age: 26 years; range: 7–59) with FVIII ≤2% and ≥8 joint haemorrhages in the year before enrolment. Aim The aim of this study was to evaluate joint bleeding episodes during the on‐demand and prophylactic study periods. Methods A post hoc analysis of joint bleeding episodes in the per protocol analysis set (n = 53) was conducted. Results The annualized joint bleeding rate (AJBR) was significantly lower for subjects treated with 12 months of SP (n = 30) or PKP (n = 23) as compared with 6 months of OD (n = 53): 55 median AJBR 0.48 [interquartile range (IQR) 1.96], 72 [1.00 (4.07)] and 1164 [38.65 (24.81)] respectively (P < 0.0001). Median AJBR was comparable during both prophylaxis arms (0.5 and 1.0 respectively). In contrast, median AJBR during on‐demand therapy was 38.7 (P < 0.0001). Conclusion Both SP and PKP significantly increased the median number of days between joint bleeding episodes compared with OD: 268.9, 182.9 and 7.4 respectively (P < 0.0001). Study subjects experienced these joint‐protective benefits of prophylaxis regardless of the number of baseline target joints.